2013
DOI: 10.1007/s11743-013-1477-x
|View full text |Cite
|
Sign up to set email alerts
|

Micellization and Interfacial Interaction Behaviors of Gemini Cationic Surfactants–CTAB Mixed Surfactant Systems

Abstract: The interfacial and micellization behaviors of binary mixtures of two gemini cationic surfactants and conventional the cetyl trimethyl ammonium bromide surfactant were studied at various molar ratios. From the equilibrium surface tension measurements, the critical micelle concentrations (CMC) data were obtained as functions of the composition. Values of the CMC were analyzed according to the regular solution model developed by Rubingh for mixed micelles. Two interaction parameters were obtained for each system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…All β M b 0 with a different α value, indicating that synergism exists resulting in the formation of mixed micelles between D821 and CTAB. In addition, all |β M | b 3 indicate that the synergism is weak due to both D821 and CTAB being positively charged quaternary ammonium ions and exhibit a repulsive interaction between cationic groups [31][32][33]. However, CTAB with a positively charged can provide additional antibacterial activity and is an appropriate synergistic additive to D821.…”
Section: Synergistic Effect Of the D821-ctab Mixed Surfactant Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…All β M b 0 with a different α value, indicating that synergism exists resulting in the formation of mixed micelles between D821 and CTAB. In addition, all |β M | b 3 indicate that the synergism is weak due to both D821 and CTAB being positively charged quaternary ammonium ions and exhibit a repulsive interaction between cationic groups [31][32][33]. However, CTAB with a positively charged can provide additional antibacterial activity and is an appropriate synergistic additive to D821.…”
Section: Synergistic Effect Of the D821-ctab Mixed Surfactant Systemsmentioning
confidence: 99%
“…Both D821 and CTAB are positively charged quaternary ammonium ions with repulsive interactions between the cationic groups, which are not beneficial for synergetic emulsification [42]. However, some studies have reported that CTAB can effectively form synergetic mixed surfactant systems with cationic surfactants [31,32]. In addition, a systematic investigation of the composition of the D821-CTAB mixed surfactants in the St/BA emulsion polymerization, and the results are shown in Table 2.…”
Section: Characteristics Of the Poly(st-co-ba) Cationic Emulsionsmentioning
confidence: 99%
See 1 more Smart Citation
“…If CMC exp is equal to the CMC ideal , the system has no interaction and the mixing of the components is ideal. The ideality indicates that there is no interaction between the different components in the mixed system (Mohamed et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…These interactions are greatest when there are similarities in the structures of their hydrocarbon chains. [38,39] Synergistic effect was observed in binary systems of cationic gemini and conventional surfactants in the micelle. Greater synergistic interaction in the micelles has been found to reduce the solubilizing capacity toward polyaromatic hydrocarbons (PAHs).…”
Section: Introductionmentioning
confidence: 99%